Faktor-Faktor Yang Berhubungan Dengan Status Gizi Balita Di Kelurahan Pangkalan Jati Kecamatan Cinere Kota Depok Tahun 2020 - Noura Azmia Tabah; Sri Wahyuningsih (Universitas Widya Gama Mahakam Samarinda, 2021)
Background: Toddler nutritional status is an important thing that must be known by every parent. Special attention needed for the growth and development of the toddler due to the fact that malnutrition during this golden period is irreversible, malnutrition in this period can also affect children's brain development in the future. Objectives: The purpose of this study is to determine what factors that related to the toddler nutritional status in Posyandu Kelurahan Pangkalan Jati Kecamatan Cinere, Depok city in year 2020. Research Metodes: The design of this study is cross sectional with a sample size 158 respondents who fit the inclusion criteria using a propotional stratified random sampling technique. Results: The result of this study, chi square showed the factors that related to the toddler nutritional status are gender variables (p value = 0.005), exclusive breastfeeding (p value = 0.003), infectious diseases (p value = 0,000), mother's occupational status ( p value = 0.004), mother's education level (p value = 0,000), family income (p value = 0,000), and number of family members (p value = 0.001). The logistic regression test results showed that the factor mostly affected toddler nutritional status in Posyandu Kelurahan Pangkalan Kecamatan Cinere, Depok City is family income (odds ratio 38.844; 95% CI 9.977-151.230). Conclusion: The factor mostly affected toddler nutritional status in Posyandu Kelurahan Pangkalan Kecamatan Cinere, Depok City is family income